Pediatricians' perspectives on COVID-19 and HPV vaccine hesitancy - Grace W. Ryan; Mary Beth Miotto; Cynthia McReynolds; Stephenie C. Lemon; Lori Pbert; Michelle Trivedi (Taylor & Francis Group, 2023)
Rises in parental vaccine hesitancy, observed during the COVID−19 pandemic, threaten public health. This is especially concerning for vaccines not typically required for school-entry, such as the vaccines for COVID−19 and human papillomavirus (HPV), both of which also have much lower rates of completion compared to other adolescent vaccines. Pediatricians are well-positioned to address vaccine hesitancy and can offer insights into parents' perspectives in this area. There is evidence that pediatricians' sharing their own vaccine stories may help to address parents' concerns; yet we have little information on pediatricians' or their children's COVID−19 vaccine uptake. To address these gaps, we conducted a cross-sectional survey about Massachusetts pediatricians' behaviors and perspectives on vaccines that face significant resistance: HPV and COVID−19 vaccines. A total of 144 people initiated the survey, and 109 participants were eligible and completed the survey. Participants reported high levels of COVID−19 vaccine uptake for themselves (97%) and their children (98%). Similarities in parents' resistance toward both vaccines were identified: fear of side effects; general vaccine resistance. Pediatricians reported a rise in vaccine hesitancy since the beginning of the COVID−19 pandemic. Future research should focus on identifying strategies to build overall vaccine confidence and streamline these efforts for pediatricians.